2019
DOI: 10.1177/0272989x19881967
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Survival Analysis Methods Used in NICE Technology Appraisals of Cancer Treatments: Consistency, Limitations, and Areas for Improvement

Abstract: Objectives. In June 2011, the National Institute for Health and Care Excellence (NICE) Decision Support Unit published a Technical Support Document (TSD) providing recommendations on survival analysis for NICE technology appraisals (TAs). Survival analysis outputs are influential inputs into economic models estimating the cost-effectiveness of new cancer treatments. Hence, it is important that systematic and justifiable model selection approaches are used. This study investigates the extent to which the TSD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 14 publications
(17 reference statements)
1
43
0
Order By: Relevance
“…It is clear that reliance solely on statistical measures of goodness of fit can result in severe bias and incorrect estimation of RMST even when 2 or more measures might agree on the optimal model, and it is reassuring that model plausibility is also usually considered in practice, although not always. 2 Our scenarios of trial followup suggested that the models preferred by the selection methods were often associated with significantly higher MSEs than the best parametric model, suggesting there is room for improvement over AIC and BIC when selecting models for extrapolation. We have shown that the difference in the underlying assumptions of the shapes of the models is an important consideration, given that the log-normal, log-logistic, and Gompertz models often provided markedly difference estimates of RMST compared to the other parametric forms, particularly in the scenarios of trial follow-up.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is clear that reliance solely on statistical measures of goodness of fit can result in severe bias and incorrect estimation of RMST even when 2 or more measures might agree on the optimal model, and it is reassuring that model plausibility is also usually considered in practice, although not always. 2 Our scenarios of trial followup suggested that the models preferred by the selection methods were often associated with significantly higher MSEs than the best parametric model, suggesting there is room for improvement over AIC and BIC when selecting models for extrapolation. We have shown that the difference in the underlying assumptions of the shapes of the models is an important consideration, given that the log-normal, log-logistic, and Gompertz models often provided markedly difference estimates of RMST compared to the other parametric forms, particularly in the scenarios of trial follow-up.…”
Section: Discussionmentioning
confidence: 84%
“…The most common approach to extrapolation in NICE appraisals is to select a single model from a range of parametric models (e.g., exponential). 1,2 Candidate models are usually compared on 2 metrics: on the goodness of fit to the observed data and on the plausibility of the extrapolations. This article considers the former, since the plausibility of extrapolations can only objectively be demonstrated when suitably mature data are available.…”
Section: Methods For Model Selectionmentioning
confidence: 99%
“…In addition, the analytical methods selected for economic evaluation in oncology have been shown to influence survival results [10], and therefore it is important for appropriate methods to be used when evaluating oncology products. However, only two previous studies have detailed the use of survival analysis in economic evaluations in oncology [11,12]. The first of these studies examined survival modeling and extrapolation techniques used in oncology submissions to the NICE in the UK before and after publication of the NICE Decision Support Unit's Technical Support Document (TSD) on survival analysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…A second study from 2019 reviewed 58 NICE technology appraisals and examined the extent to which recommendations made in the NICE Decision Support Unit's TSD on survival analysis have been followed since its publication [11]. The authors found that while there were increases in validation of the results using data and/or clinical opinion following publication of the TSD, the proportion of submissions that adhered to the TSD recommendations did not change substantively over time.…”
Section: Introductionmentioning
confidence: 99%
“…Time-to-event outcomes are routinely modeled in health technology appraisals by fitting parametric models to observed data and extrapolating until no patients are predicted to remain at risk of an event. 1,2 These models are commonly used to predict the amount of time patients spend in particular health states, either through the estimation of transition probabilities or mean survival times, depending on the type of economic model. The time in each health state is combined with a health-related quality-of-life utility value and the costs of factors including therapy, disease management, and adverse events to produce an overall estimate of the cost-effectiveness of a treatment relative to a comparator.…”
mentioning
confidence: 99%